Bis(μ-2-methylquinolin-8-olato)-κ3N,O:O;κ3O:N,O-bis[(acetato-κ2O,O′)lead(II)] (Acta Crystallographica Section E, 2009)
Both independent PbII atoms in the title compound, [Pb2(C10H8NO)2(C2H3O2)2], are chelated by acetate and substituted quinolin-8-olate anions; the O atoms of the quinolin-8-olates also bridge to confer a five-coordinate status to each metal center. The geometry approximates a distorted Ψ-fac octahedron in which one of the sites is occupied by a stereochemically active lone pair.